Patient-related Factors and Perioperative Outcomes Are Associated with Self-Reported Hospital Rating after Spine Surgery. Issue 3 (March 2020) - Mets, Elbert J.; Mercier, Michael R.; Hilibrand, Ari S.; Scott, Michelle C.; Varthi, Arya G.; Grauer, Jonathan N.
Abstract: Background: Since 2013, the Centers for Medicare & Medicaid Services has tied a portion of hospitals' annual reimbursement to patients' responses to the Hospital Consumer Assessment and Healthcare Providers and Systems (HCAHPS) survey, which is given to a random sample of inpatients after discharge. The most general question in the HCAHPS survey asks patients to rate their overall hospital experience on a scale of 0 to 10, with a score of 9 or 10 considered high, or "top-box." Previous work has suggested that HCAHPS responses, which are meant to be an objective measure of the quality of care delivered, may vary based on numerous patient factors. However, few studies to date have identified factors associated with HCAHPS scores among patients undergoing spine surgery, and those that have are largely restricted to surgery of the lumbar spine. Consequently, patient and perioperative factors associated with HCAHPS scores among patients receiving surgery across the spine have not been well elucidated. Questions/purposes: Among patients undergoing spine surgery, we asked if a "top-box" rating on the overall hospital experience question on the HCAHPS survey was associated with (1) patient-related factors present before admission; (2) surgical variables related to the procedure; and/or (3) 30-day perioperative outcomes. Methods: Among 5517 patients undergoing spine surgery at a single academic institution from 2013 to 2017 and who were sent an HCAHPS survey, 27% (1480) returned the survey and answered the question related to overall hospital experience. A retrospective, comparative analysis was performed comparing patients who rated their overall hospital experience as "top-box" with those who did not. Patient demographics, comorbidities, surgical variables, and perioperative outcomes were compared between the groups. A multivariate logistic regression analysis was performed to determine patient demographics, comorbidities, and surgical variables associated with a top-box hospital rating. Additional multivariate logistic regression analyses controlling for these variables were performed to determine the association of any adverse event, major adverse events (such as myocardial infarction, pulmonary embolism), and minor adverse events (such as urinary tract infection, pneumonia); reoperation; readmission; and prolonged hospitalization with a top-box hospital rating. Results: After controlling for potential confounding variables (including patient demographics), comorbidities that differed in incidence between patients who rated the hospital top-box and those who did not, and variables related to surgery, the patient factors associated with a top-box hospital rating were older age (compared with age ⩽ 40 years; odds ratio 2.2, [95% confidence interval 1.4 to 3.4]; p = 0.001 for 41 to 60 years; OR 2.5 [95% CI 1.6 to 3.9]; p < 0.001 for 61 to 80 years; OR 2.1 [95% CI 1.1 to 4.1]; p = 0.036 for > 80 years), and being a man (OR 1.3 [95% CI 1.0 to 1.7]; p = 0.028). Further, a non-top-box hospital rating was associated with American Society of Anesthesiologists Class II (OR 0.5 [95% CI 0.3 to 0.9]; p = 0.024), Class III (OR 0.5 [95% CI 0.3 to 0.9]; p = 0.020), or Class IV (OR 0.2 [95% CI 0.1 to 0.5]; p = 0.003). The only surgical factor positively associated with a top-box hospital rating was cervical surgery (compared with lumbar surgery; OR 1.4 [95% CI 1.1 to 1.9]; p = 0.016), while nonelective surgery (OR 0.5 [95% CI 0.3 to 0.8]; p = 0.004) was associated with a non-top-box hospital rating. Controlling for the same set of variables, a non-top-box rating was associated with the occurrence of any adverse event (OR 0.5 [95% CI 0.3 to 0.7]; p < 0.001), readmission (OR 0.5 [95% CI 0.3 to 0.9]; p = 0.023), and prolonged hospital stay (OR, 0.6 [95% CI 0.4 to 0.8]; p = 0.004). Conclusions: Identifying patient factors present before surgery that are independently associated with HCAHPS scores underscores the survey's limited utility in accurately measuring the quality of care delivered to patients undergoing spine surgery. HCAHPS responses in the spine surgery population should be interpreted with caution and should consider the factors identified here. Given differing findings in the literature regarding the effect of adverse events on HCAHPS scores, future work should aim to further characterize this relationship. Level of Evidence: Level III, therapeutic study.